She left : a novel - Grey, Stacie (Poisoned Pen Press, 2024)
"As a teenager, Amy Therese Brewer argued with her friends and stormed out of a party-moments before the five other teens were brutally murdered. Now, on the anniversary of those deaths, ten people with connections to the crime have been invited to a remote cliffside house by a journalist looking to do a story about the so-called Memorial Day Massacre. But the group quickly learns the event is not what it seems. As a storm closes in and guests begin to die, Therese realizes there is someone in the house who knows more than they admit about what happened that night long ago, and they will stop at nothing to protect their secrets"--